Proteome-wide tagging with an H2O2 biosensor reveals highly localized and dynamic redox microenvironments - Kritsiligkou, Paraskevi; Bosch, Katharina; Shen, Tzu Keng; Meurer, Matthias; Knop, Michael; Dick, Tobias P. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Hydrogen peroxide (H2O2) sensing and signaling involves the reversible oxidation of particular thiols on particular proteins to modulate protein function in a dynamic manner. H2O2 can be generated from various intracellular sources, but their identities and relative contributions are often unknown. To identify endogenous “hotspots” of H2O2 generation on the scale of individual proteins and protein complexes, we generated a yeast library in which the H2O2 sensor HyPer7 was fused to the C-terminus of all protein-coding open reading frames (ORFs). We also generated a control library in which a redox-insensitive mutant of HyPer7 (SypHer7) was fused to all ORFs. Both libraries were screened side-by-side to identify proteins located within H2O2-generating environments. Screening under a variety of different metabolic conditions revealed dynamic changes in H2O2 availability highly specific to individual proteins and protein complexes. These findings suggest that intracellular H2O2 generation is much more localized and functionally differentiated than previously recognized.
Im Titel ist die Zahl 2 tiefgestellt
Gesehen am 22.03.2024